الإنشاء في كتاب سيبويه دراسة تداولية - بن ساسي, مناوي,وئام خيرة (University of El-oued, 2022)
يتناول موضوع مذكرتنا دراسة تداولية للإنشاء نحويا في كتاب سيبويه, اعتمدنا فيها على المنهج الوصفي للأساليب الإنشائية في الفكر النحوي والبلاغي العربي في مقابل الأفعال الكلامية في الفكر اللساني الغربي, وبذلك قسم عملنا الى قسمين نظري يتقصى المفاهيم والمصطلحات والتطبيقي في النحو السيبويهي لرؤية المتقاربة للأفعال اللغوية بالمنظور التداولي, فتحققت بذلك اهم نتائج البحث التي أردناها. The topic of our memo deals with a deliberative study of the creation of grammatical in the book of Sibawayh, in which we relied on the descriptive approach to the construction methods in grammatical and rhetoric thought in exchange for verbal acts in Western linguistic thought, and thus our work was divided into two theoretical parts that investigate concepts, terms and applied in the Sibwehi grammar to see the convergence of linguistic actions in perspective Trading, I achieved the most important search results that we wanted
Keywords: Construction - Sibawayh - a deliberative study; الإنشاء - سيبويه - دراسة تداولية